EFEKTIVITAS PENGUNAAN APLIKASI SIPEDE DALAM MENINGKATKAN EFISIENSI PENGELOLAAN SURAT PADA KEJAKSAAN NEGERI SUMEDANG - Mercy Nur Fauziyah (LPPM UNSAP, 2026)
This study aims to determine the effectiveness of using the SIPEDE application (Electronic Correspondence and Disposition System) in improving the efficiency of correspondence management at the Sumedang District Prosecutor's Office, identify the obstacles encountered during its implementation, and the efforts made to overcome these obstacles. The development of digitalization in public administration requires every government agency to adopt electronic-based information systems to support transparency, speed, and accuracy in bureaucratic work. This study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The research subjects were employees of the Sumedang District Prosecutor's Office directly involved in the use of the SIPEDE application. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of the SIPEDE application plays a role in accelerating the document management process, improving work efficiency, and creating a well-organized documentation system. However, there are several challenges, such as insufficient socialization and training, weak periodic evaluations, and the lack of optimal standard operating procedures (SOPs). To address these challenges, the Sumedang District Prosecutor's Office has implemented measures to enhance human resource capacity, conduct regular system evaluations, and strengthen internal policies related to the use of the application. This study is expected to serve as a reference for other government agencies in developing and implementing effective digital information systems for administrative document management.